SARS-CoV-2 Whole-Genome Sequencing by Ion S5 Technology—Challenges, Protocol Optimization and Success Rates for Different Strains - Maria Szargut; Sandra Cytacka; Karol Serwin; Anna Urbańska; Romain Gastineau; Miłosz Parczewski; Andrzej Ossowski (Viruses, 2022)
The COVID-19 pandemic demonstrated how rapidly various molecular methods can be adapted for a Public Health Emergency. Whether a need arises for whole-genome studies (next-generation sequencing), fast and high-throughput diagnostics (reverse-transcription real-time PCR) or global immunization (construction of mRNA or viral vector vaccines), the scientific community has been able to answer all these calls. In this study, we aimed at the assessment of effectiveness of the commercially available solution for full-genome SARS-CoV-2 sequencing (AmpliSeq™ SARS-CoV-2 Research Panel and Ion AmpliSeq™ Library Kit Plus, Thermo Fisher Scientific). The study is based on 634 samples obtained from patients from Poland, with varying viral load, assigned to a number of lineages. Here, we also present the results of protocol modifications implemented to obtain high-quality genomic data. We found that a modified library preparation protocol required less viral RNA input in order to obtain the optimal library quantity. Concurrently, neither concentration of cDNA nor reamplification of libraries from low-template samples improved the results of sequencing. On the basis of the amplicon success rates, we propose one amplicon to be redesigned, namely, the r1_1.15.1421280, for which less than 50 reads were produced by 44% of samples. Additionally, we found several mutations within different SARS-CoV-2 lineages that cause the neighboring amplicons to underperform. Therefore, due to constant SARS-CoV-2 evolution, we support the idea of conducting ongoing sequence-based surveillance studies to continuously validate commercially available RT-PCR and whole-genome sequencing solutions.